2021
DOI: 10.1016/j.commatsci.2021.110281
|View full text |Cite
|
Sign up to set email alerts
|

MAST-SEY: MAterial Simulation Toolkit for Secondary Electron Yield. A monte carlo approach to secondary electron emission based on complex dielectric functions

Abstract: is an open-source Monte Carlo code capable of calculating secondary electron emission ~~mg mput data ge~erate~ entirely from first principle (density functional theory) calculations. It utilizes the complex dielectric function and Penn's theory for inelastic scattering processes and relativistic Schrodinger theory by means of a partial-wave expansion method to govern elastic 'scattering. It allows the user to include explicitly calculated momentum dependence of the dielectric func~ion, as well as to utilize fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Previous works have demonstrated that some of these parameters, for example SEECs, can be determined under plasma exposure by computationally assisted diagnostics [39] and combinations of current measurements and modeling [40,41]. Alternatively, they can be calculated based on ab initio models [42][43][44][45]. Typically, however, such surface coefficients are either neglected, guessed, or taken from beam-experiments performed under ultra-high vacuum conditions without plasmas that typically modify the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Previous works have demonstrated that some of these parameters, for example SEECs, can be determined under plasma exposure by computationally assisted diagnostics [39] and combinations of current measurements and modeling [40,41]. Alternatively, they can be calculated based on ab initio models [42][43][44][45]. Typically, however, such surface coefficients are either neglected, guessed, or taken from beam-experiments performed under ultra-high vacuum conditions without plasmas that typically modify the surface.…”
Section: Introductionmentioning
confidence: 99%
“…29 Extensions of DFT-like time dependent density functional theory (TDDFT) attempt to address this and can give results in good comparison to experiments for molecules and smaller structures. 30,31 TDDFT has been applied to solids like Cu and has been claimed to give better comparison with experiments compared to optical data models, 32,33 but in such a material, even ground-state DFT gives good agreement with the experiments. 27 Electrons in a metal like Cu experience more screening, which makes many-body effects from excitations less significant, 29 so it is unclear what improvements to the IMFP arise from TDDFT alone.…”
Section: Model Improvementmentioning
confidence: 99%
“…With the development of science and technology, simulation and modelling techniques are becoming more and more mature and stable. The Monte Carlo simulation method is a powerful tool to study the phenomenon of secondary electron emission [19][20][21][22]. This method is characterized by higher efficiency, faster time, and lower cost than experimental measurements.…”
Section: Introductionmentioning
confidence: 99%